Professores de História em cenários de experiência - Jezulino Lucio Mendes Braga (2014)
The main theme of this thesis is the sensory experiences of History teachers at the Museu de Artes e Ofícios (MAO) in the city of Belo Horizonte, Minas Gerais. We analyzed experiences of pedagogical use of the museum and the relationships that teachers establish with the exhibition. We aimed to comprehend which conceptions of history, memory and narrative are present in the activities designed to teach through the exhibition. This analysis is shown through data collected from structured interviews with questionnaires and narrative interviews done in contact with the exhibition at MAO.